2019
DOI: 10.15760/trec.227
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Examination of Electronic Wayfinding Technology for Visually Impaired Travelers in an Urban Environment

Abstract: In this project, we distilled an inventory of smartphone-based electronic travel aid technology for the wayfinding of visually impaired travelers in an urban environment based on a thorough review of software marketplaces and the academic literature. Subsequently, we solicited structured input from domain experts and visually impaired individuals on their experiences and evaluations pertaining to personal telecommunication technology for safe and efficient wayfinding. The insights gained from this project are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…This brief report represents the experiences of a bounded group of participants living in an urban environment, who identify as Deafblind and use TASL or close range visual ASL for communication. The Deafblind group's responses on which particular wayfinding apps they used were captured as a part of a broader investigation on wayfinding apps (Swobodzinski and Parker, 2019). The perspectives of participants were further examined within this article to amplify the voices of individuals who consider themselves culturally and linguistically Deafblind, those who are not often included in OandM research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This brief report represents the experiences of a bounded group of participants living in an urban environment, who identify as Deafblind and use TASL or close range visual ASL for communication. The Deafblind group's responses on which particular wayfinding apps they used were captured as a part of a broader investigation on wayfinding apps (Swobodzinski and Parker, 2019). The perspectives of participants were further examined within this article to amplify the voices of individuals who consider themselves culturally and linguistically Deafblind, those who are not often included in OandM research.…”
Section: Discussionmentioning
confidence: 99%
“…In this article, we report on the lived experiences of adults who are Deafblind pertaining to the challenges and opportunities afforded by personal mobile phones and wayfinding apps for urban environments. While the overall findings from our study, including an inventory of wayfinding apps that participants identified, have been made available in the final study report (Swobodzinski and Parker, 2019), qualitative themes from our research activities with the Deafblind participants have not been explored in detail. Instead, these are conveyed in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…However, with asynchronous apps the user and application interact in nonreal time and they only include static data for maps and route information. It is also to be noted that, in regard to the mobile apps for navigation, plenty of mobile apps such as Be My Ayes and Aira offer orientation in an urban setting for pedestrians with visual as well as hearing impairments [22].…”
Section: The Contribution Of Mobile Apps To Transportationmentioning
confidence: 99%
“…The case study discussed in this paper is a part of a larger research project that aims to assess the degree of seamlessness of the wayfinding experiences of visually impaired or blind pedestrian travelers, with a particular focus on those who are deafblind, as it comes to negotiating realistic pedestrian routes. The project builds upon prior work of the lead authors on the use of mobile wayfinding technology by low-vision, blind, and deafblind users (Swobodzinski and Parker, 2019;Parker et al, 2020). Our focus in the paper at hand is on the description and discussion of the qualitative and quantitative factors, both observed and emerged, that informed the wayfinding behavior of the deafblind participant in our case study.…”
Section: Introductionmentioning
confidence: 99%
“…Such separation does not apply to typical human travel (Kim and Lehto, 2013;Kray et al, 2013;Winters et al, 2015) and it is one of the factors that inhibits a consolidation of mobile wayfinding software, functionality, and data models for seamless wayfinding through outdoor, indoor, and transitional spaces (Vanclooster et al, 2016;Wagner et al, 2017;Yan et al, 2019). As it stands, few mobile wayfinding solutions consider the information needs of visually impaired, blind, and deafblind individuals, and the desired functionality remains fragmented (Swobodzinski and Parker, 2019).…”
Section: Introductionmentioning
confidence: 99%